The The Link Between Prolonged Sitting and UTIs: A Cross-Sectional Study of Bank Tellers in Tarakan, Indonesia - Prastyo, Yogho; Dwiningtias, Dini; Yulia, Ifa (Jurnal Ilmu Kesehatan, 2024)
Urinary tract infections (UTIs), which are common in humans, can be influenced by a lack of physical activity, as experienced by office workers, including bank employees, who tend to spend long periods sitting in front of desks and computers. The aim of this study was to determine the relationship between prolonged sitting and UTIs among Bank Employees in North Kalimantan, Tarakan City. This was an analytical observational study with a cross-sectional design. Data were collected using questionnaires from 64 subjects selected through random sampling. The results showed that 33 (48.4%) experienced UTIs. Prolonged sitting for ≥5 hours contributed to 44 subjects (68.8%). The chi-square test analysis showed a relationship between prolonged sitting and UTIs among Bank Employees in North Kalimantan, Tarakan City (p-value = 0.02). The conclusion of this study is that there is a relationship between prolonged sitting and UTIs among Bank Employees. To reduce the risk of UTIs, it is recommended that bank employees regularly stand or walk.